Lower Ionospheric Perturbations Associated with Lightning Activity over Low and Equatorial Regions - Dayanand Bhaskar; Rajat Tripathi; Mahesh N. Shrivastava; Rajesh Singh; Sudipta Sasmal; Abhirup Datta; Ajeet Kumar Maurya (Atmosphere, 2025)
We present lightning-induced ionospheric perturbations in narrowband very-low-frequency (VLF) signals from the transmitters NWC (21.82° S, 114.17° E, 19.8 kHz) and VTX (8.4° N, 77.8° E, 18.6 kHz) recorded at the low-latitude station Dehradun (DDN; 30.3° N, 78.0° E) over a 12-month period from September 2020 to October 2021. Early/slow VLF events, VLF LOREs, and step-like VLF LOREs associated with lightning were analyzed for their onset and recovery times. This study utilized data from the World Wide Lightning Location Network (WWLLN), which provides lightning locations and energy estimates. The results show that early/slow VLF events occur most frequently, accounting for approximately 68% of cases, followed by VLF LOREs at 12%, and step-like VLF LOREs at 10%. Furthermore, we observed that 100% of the VLF perturbing events occurred during the nighttime, which is not entirely consistent with previous studies. Moreover, more than 60% of VLF LOREs were associated with lightning energies of approximately 1 kJ, and about 40% were associated with lightning energies of ~10 kJ. Step-like VLF LOREs were linked to WWLLN energies between 1 and 5 kJ. The observed WWLLN energy range is somewhat lower than the energies reported in previous studies. Scattering characteristics revealed that 87.3% of events were associated with wide-angle scattering, while approximately 12.6% were linked to narrow-angle scattering. LWPC version 2.1 was used to simulate these perturbing events and to estimate the reflection height (H′, in km) and the exponential sharpness factor (β, in km−1) corresponding to changes in D-region electron density. The reflection height (H′, in km) and the exponential sharpness factor (β, in km−1) of the D-region varied from 83 to 87 km and from 0.42 to 0.79 km−1 for early/slow VLF events, from 83 to 85 km and from 0.5 to 0.75 km−1 for step-like VLF LOREs, and from 81 to 83 km and from 0.75 to 0.81 km−1 for VLF LOREs, respectively.